First language transfer in the acquisition of English prepositions by Jordanian EFL learners - Yazan Shaker Okla Almahammed (Universiti Sains Islam Malaysia, 2024)
Language transfer has an immense influence on all subsystems of the second language. Traditionally, the concept of language transfer was viewed as the effect of first language on the acquisition of the second language. Language transfer can be categorized into two types; negative transfer which stems from differences between first language and target language and positive transfer which results from similarities between two languages in contrast. This study aimed primarily at investigating negative Arabic transfer in the acquisition of English prepositions by Jordanian EFL learners. English prepositions constitute a learning problem for Jordanian EFL learners. Fill-in-the-blank test, grammaticality judgment and correction task and cloze test were used to collect data. A total of 355 Jordanian EFL learners at bachelor degree level participated in this quantitative study. The respondents were selected from ten universities in Jordan via cluster random sampling procedures. The study revealed the following main findings; negative Arabic transfer affected the acquisition of English prepositions. About 35.2% of prepositional errors resulted from negative Arabic transfer. The acquisition of English prepositions was influenced noticeably by intralingual interference. It was found that 64.8% of prepositional errors were ascribed to intralingual interference. The results also revealed that preposition combinations was the most difficult usage of English prepositions for Jordanian EFL learners. The proportion of errors in the use of preposition combinations was 65.2%. With reference to the use of pied-piping and preposition stranding in interrogatives, the analysis displayed that the respondents showed no preference of pied piping over preposition stranding and vice versa. The results of the study supported the moderate position, which holds that both language transfer and intralingual interference interact in shaping the acquisition of English prepositions. The study has some implications for textbook authors and the teaching of English prepositions to EFL learners.